The impact of sandy soil physico-chemical properties towards urban lakes eutrophication and inorganic pollutant status - Wan Sulaiman, Wan Syibrah Hanisah; Othman, Rashidi; Hj. Baharuddin, Zainul Mukrim (2018)
Variety of soil type in Malaysia has contributed to the difference of soil properties dissolved in the water and the concern of soil problem in Malaysia involving from laterite, sandy, acid sulfate and organic soil type that required monitoring action. The physico-chemical properties assessment tools that were used to evaluate the water sample area consist of pH, temperature, dissolved oxygen (DO), total suspended solids (TSS), chemical oxygen demand (COD), biological oxygen demand (BOD) and ammoniacal nitrogen(NH3-N). For heavy metals, 10 elements had been selected based on Malaysia Environmental Quality Report for further evaluation that consists of (Al, Cr, Mn, Fe, Co, Ni, Cu, Zn, Cd, Pb). Physico chemicals properties for water were measured in situ and in the laboratory before calculated with WQI formula to define the water quality index classification. Further analysis was prepared by using ICP-MS and ANOVA for heavy metals assessment equally for soil and water. The result obtained by in situ experiment and laboratory showed the average of WQI for sandy soil in urban lake was in class IV as average that suitable only for irrigation and the status of water mostly were polluted as amount of the high value in BOD (81.62mg/L), COD (23.53mg/L) and NH3-N (0.44mg/L). The level of TSS was low ( 27.18mg/L) as sandy soil particle less influence for soil movement into the water. As for the result of heavy metals, the composition varied in water but several elements exceeded the natural level such as Al (0.07mg/L), Cr (0.3mg/L), Ni(0.11mg/L), Cu(0.02mg/L) and Pb (1.43mg/L) as responding to the character of porosity in sandy soil. Meanwhile, two significant elements were found in sandy soil which was Al(157.95mg/kg) and Fe(156.17 mg/kg) and becomes a signature indicator. As a conclusion, evaluation influence of sandy soil physico-chemicals properties of water and heavy metals concentration are significant for water quality monitoring action to minimize water quality degradation in Malaysia.